Construção e validação de cenário de simulação clínica sobre a influência sensorial da unidade de terapia intensiva neonatal no sono do recém-nascido pré-termo - Oliveira, Débora Teles de (2024)
In neonatal intensive care units, the environment can affect the quality of sleep of preterm newborns due to noise, handling, and brightness. The intended purpose of this study was to develop and validate a simulated scenario about the influence of the sensory environment of the neonatal intensive care unit on the sleep of hospitalized preterm newborns. A methodological study developed in three phases: 1. Scoping review; 2. Development of the clinical case and simulation scenario and 3. Semantic validation of the scenario with experts. Approved by the Research Ethics Committee of the Federal University of Ceará/CAAE under No. 6462922.9.0000.5054. The scoping review was carried out following the recommendations of the Joanna Briggs Institute (JBI) and registered with the Open Science Framework under registration number 10.17605/OSF.IO/3EPRT. The search was carried out in eight indexed databases: MEDLINE/Pubmed, Web of Science, SCOPUS, Cochrane, CINAHL, EMBASE, LILACS, SCIELO, and PsycInfo. Grey literature searches were carried out in CTD, BDTD, OATD, NDTLTD, and Open Gray. In the end, the review consisted of 24 articles obtained from the databases and three gray literature publications. The studies included presented the difficulties of the neonatal environment, such as loud noises, strong lighting and excessive touching, and the non-pharmacological methods that can promote neonatal sleep, such as ear plugs, white noise, mother's voice and lullaby music for the sense of hearing, sucking with sucrose for taste, gentle human touch and Yakson touch, massage, kangaroo care position, nest, hammock, co-sleeping and position in the incubator in the touch category and covering the incubator in the sense of sight. From these results, the clinical case and simulation scenario "The sensory influence of the NICU on the sleep of the preterm infant" were constructed. After development, the semantic validation and content validation phases began, the first with three experts and the second with nine experts with experience in neonatology, the NICU, and/or simulation. The research data was stored in a database and analyzed by calculating the Content Validity Index to determine the degree of agreement of the clinical case. The instrument was adapted from Góes et al. (2017) and comprises four categories: language, content, objective, and applicability. In the semantic validation, the clinical case achieved an overall agreement of 0.80, and the content validation of the simulation scenario achieved an overall agreement of 0.91. Among the modifications requested and implemented in the scenario, the following stand out: a description of the NICU environment and the professional routine, corrections to vital signs, and a modification to the ventilatory support provided by the PTNB. The achieved validity index indicates the quality of the case and simulation scenario in terms of semantics. After a thorough evaluation of the intended audience, the scenario can be replicated in both undergraduate and postgraduate teaching centers, considering its level of realism, and fostering the teaching-learning process of the students. These characteristics indicate that clinical simulation is a suitable teaching methodology with innovative potential, which can be employed in health education, thereby facilitating the training of exceptional professionals.